Evaluation of CD4+ T Lymphocyte Counts to Predict Survival of ICU Patients with Sepsis Using Sepsis-3 Criteria: A Prospective Cohort Study - Guoge Huang; Xusheng Li; Chunmei Zhang; Haizhong Li; Mengling Jian; Chunyang Huang; Yingqin Zhang; Luhua Xian; Hongke Zeng; Yuanyuan Xia; Wenqiang Jiang (Emergency Medicine International)
Background. Sepsis remains a major health condition with a high mortality rate that may be related to immunosuppression. T lymphocyte subsets may reflect the immune function of sepsis patients. The purpose of this study was to investigate the predictive value of CD4+ T lymphocyte counts of ICU patients for their short-term prognosis. Methods. We conducted a prospective, observational cohort study in a general ICU and enrolled patients with sepsis using the Sepsis-3 criteria. Peripheral blood samples were collected within 24 hours of enrollment or measurement of blood cell analysis and biomarkers of CD4+ T lymphocytes and CD8+ T lymphocytes. Severity was classified by the Acute Physiology and Chronic Health Evaluation II and Sequential Organ Failure Assessment (SOFA) scores. The primary outcome was 28-day mortality. Results. A total of 100 patients with sepsis were enrolled and analyzed. CD4+ T lymphocyte counts gradually decreased based on 28-day mortality (p<0.001). Similarly, multivariate logistic regression analysis showed that only CD4+ T lymphocyte counts were an independent predictor of 28-day mortality in sepsis patients. The area under the receiver operating characteristic curve of the combination of CD4+ T lymphocyte counts and the SOFA score was 0.78. Conclusion. Our study demonstrated that CD4+ T lymphocyte counts are associated with 28-day mortality. A combination of CD4+ T lymphocyte counts with the SOFA score increased the predictive accuracy for 28-day mortality.